Pendampingan Kelompok Calon Guru Dalam Membuat Bahan Ajar Berbasis Artificial Intelligence - Desy Safitri; Sujarwo; Nurzengky Ibrahim; Arita Marini; Anggi Saputri; Iqbal Pratama (Indo Publishing, 2025)
The development of digital technology requires teachers to be able to integrate artificial intelligence into learning. Not all teachers understand the creation of AI-based teaching materials, considering that not all teachers understand and comprehend the methods and mechanisms of using artificial intelligence to assist in learning, especially in creating digital teaching materials. Teacher competencies must be continuously upgraded so they can innovate in learning, considering that the management of learning programs will experience changes along with the development of community culture and technology. Mentoring groups of prospective teachers in creating AI-based teaching materials aims to provide mentoring to groups of prospective teachers in designing and developing AI-based teaching materials as an effort to improve professional competence in the digital era. The methods used in this activity include training, technical guidance, and direct practice with a participatory approach. The results of the activity show an increase in participants' understanding of the concept of AI in education, the ability to design AI-based digital teaching materials, and the growth of creativity and innovation in designing learning that is adaptive to the needs of 21st-century learning.